Perancangan dan Analisis Aliran Udara Sistem Ducting Cloud Kitchen dengan Metode Computational Fluid Dynamics: Design and Analysis of Cloud Kitchen Ducting System Air Flow using Computational Fluid Dynamics Method - Robin Tan; Steven Darmawan; Harto Tanujaya (Jurnal Asiimetrik: Jurnal Ilmiah Rekayasa Dan Inovasi, 2023)
Cloud Kitchen is a commercial kitchen that serves food for delivery or takeaway without dine-in customers. Because the cloud kitchen consists of many kitchens, good air circulation is needed. The total volume of the 15 kitchen units in the cloud kitchen is 249.8 m3, so to meet commercial kitchen standards that have a minimum Air Change per Hour (ACH) value of 30 ACH, an air change of 4410 m3/h with a ducting system is required. From the simulation results, the air velocity distribution in the ducting ranges from 0 m/s to 92.426 m/s, while the pressure distribution in the ducting ranges from -578.824 Pa to 11639.58 Pa, and the distribution of air temperature in the ducting ranges from 49.8°C to 65.167°C. The chosen exhaust fan is a CKE brand centrifugal fan with type CKE DGB-4.5#-NO and an exhaust capacity of 5712–10562 m3/h.